Pengaruh Perilaku Belajar terhadap Tingkat Pemahaman Akuntansi dengan Kecerdasan Emosional sebagai Variabel Pemoderasi - Agung Kresnandra, Anak Agung Ngurah (E-Jurnal Akuntansi, 2019)
The purpose of this study was to determine  the effect of each variable of learning behavior and emotional quotient at accounting understanding level, and the influence of emotional quotient  moderation on the interaction of learning behavior, at accounting understanding level. Sample selection using purposive sampling for 87 samples. Accounting understanding level data is proxied by the average final grade of accounting subjects in the MAKSI program collected from the SIMAK Unud program, while learning behavior and emotional quotient data are response data collected using questionnaires that have met the validity and reliability tests. All data have met the classical assumption test and the regression model has fulfilled the model feasibility test. Regression test results show that each variable of learning behavior and emotional quotiente has a positive and significant effect on the level of accounting understanding, besides that emotional quotiente increases the influence of learning behavior on accounting understanding level. Keywords : Accounting understanding level, emotional quotient, learning behavior.